Mentoring the Development of Mental Health Systems in Schools - Sigit Sanyata; Natri Sutanti; Nanang Erma Gunawan; Suwarjo Suwarjo; Cut Munika Bastia Ramadani (International Journal Of Community Service, 2024)
This community service program aims to provide assistance to guidance and counseling teachers who are expected to become pioneers of the school mental health system. The emergence of increasingly complex mental health problems in schools cannot only be handled in responsive and curative ways but also need to be accompanied by preventive efforts from the school. By using the paradigm of positive psychology and positive education through the PROSPER model, guidance and counseling teachers and schools in general are able to collect resources to build a mental health system in schools. The PROSPER model consists of seven components, namely positivity, relationships, outcomes, strength, purpose, engagement, and resilience. The partners selected for this community service are guidance and counseling teachers at junior high schools in the Karanganyar area under the auspices of the Karanganyar Regency Education and Culture Office. The number of participants who attended was 30 guidance and counseling teachers from both private and public schools in this area. The assistance carried out was carried out over a period of 3 months starting with initial coordination, provision of materials, workshops and assistance and monitoring. Initial coordination was carried out through the WhatsApp group media, then the provision of materials was carried out offline. This material provision activity was then continued with a workshop on preparing SOPs for implementing the PROSPER model. It is hoped that after participating in this program, target partners will have the capacity to develop mental health systems and implement them independently and sustainably. The outputs in this PkM include mandatory outputs, namely partner cooperation letters, IA scripts, print and social media publications, and PkM activity posters.